What Matters Most for Education Resilience : A Framework Paper - Reyes, Joel (World Bank, Washington, DC, 2014)
This paper presents the tools developed under the Education Resilience Approaches (ERA) program and several key principles that guide the application of a resilience process. The tool offer a systematic process to improve education system alignment to a resilience-based approach and ensure relevant quality education services for learners affected by difficult contexts, especially conflict and violence. The annexes provide more detail on how the tools can help align education strategies, plans and services in the area of access, learning quality, equity, capacity building and participation, amongst other education goals.